348 Virtual Patient Assessment for Hand Fracture Management: A Departmental Analysis of Financial and Clinical Implications. (4th May 2021) - Roberts, N; Totty, J; Pinder, R
Abstract: Introduction: The COVID-19 pandemic demanded reduced face-to-face (FTF) contact. Our department integrated virtual assessment into the incoming referral pathway to enable continuation of high-quality care. This study aimed to assess any potential efficiency benefit of this change in service whilst ensuring no compromise to clinical outcomes. Method: A prospective analysis was undertaken of all hand fractures referred virtually during a seven-week period starting at the initiation of national lockdown. Cost analysis using NHS reference costs, inflated to 2019/20 prices, was performed. Clinical performance was assessed using the British Society for Surgery for the Hand (BSSH) Standards for Open and Closed Hand Fractures. Results: Seventy-six hand fractures were referred; FTF attendance was avoided in 35 cases, with an estimated per-patient cost saving of £179.16. Of the 33 patients who attended FTF, 13 achieved same day non-operative treatment; 20 underwent operative intervention with 95% compliance to BSSH standards. No complications occurred. Conclusions: Our pilot model demonstrates potentially significant cost savings of £6270 over a relatively short period, as well as clinical non-inferiority. This supports sustained integration of virtual patient assessment in the 'new normal'. Further work across all disciplines is needed to define acceptable limits of telemedicine and new avenues for potential benefit.